Synthesis and Antibacterial Activity of New Chalcones Bearing an Imidazo[ 1,2-a]pyridine Moiety - Soltani, Siavash S.; Farnia, S. Morteza F.; Foroumadi, Alireza (Current Chemical Biology, 2021)
Aim and Objective: Herein, A series of new imidazo[1,2-a]pyridine-chalcone derivatives 3a-m were designed and synthesized to find a new class of antibacterial agents. These compounds were prepared by the aldol condensation of 2-phenylimidazo[1,2-a]pyridine-3-carbaldehyde 2a-b with acetophenone derivatives and other aromatic acetyls. High reaction yields were obtained in a short reaction time, through applying this multi-step pathway. Materials and Methods: In vitro antibacterial activities of the synthesized imidazo[1,2-a]pyridinechalcones were measured against S. aureus, B. subtilis and E. coli with MIC values of 32 -128 μg/mL. Finally, essential structural analyses such as CHN and NMR spectroscopies were used to identify the synthesized chalcones based on imidazo[1,2-a]pyridine derivatives. Results: The results showed that most of the products presented moderate to good antibacterial activities. Compounds 3b, 3d, 3g, 3l and 3m revealed obvious potency against S. aureus, B. subtilis and E. coli with MIC values of 32 μg/mL and 64 μg/mL, which were better when compared with other chalcones. Conclusion: The synthesized antibacterial compounds were obtained with appealing advantages such as high purity, simple pathway, good to excellent yields, inexpensive and easy availability of materials as well as good activities against bacteria. So in this work, a new class of antibacterial chalcones based on imidazo[1,2-a]pyridine has been reported.
Keywords: chalcones